2021
DOI: 10.1017/wet.2021.55
|View full text |Cite
|
Sign up to set email alerts
|

Investigating low-dose herbicide programs for goosegrass (Eleusine indica) and smooth crabgrass (Digitaria ischaemum) control on creeping bentgrass greens

Abstract: Only four herbicides are registered for smooth crabgrass or goosegrass control on creeping bentgrass golf putting greens. None of the four herbicides control weedy grasses for the entire season or control weeds postemergence when applied once at labeled rates. Three of these have product labels that prohibit repeated use or application during stressful summer conditions. We hypothesized frequently applying herbicides at low doses could provide season-long control of summer grasses while minimizing turf injury.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Although the mechanism for reduction in topramezone goosegrass control by chlorothalonil-containing products cannot be ascertained through this research, Lancaster et al (2005a) found that chlorothalonil reduces sethoxydim and clethodim absorption by approximately 14% when applied in mixture. A similar reduction in topramezone absorption would be expected to reduce goosegrass control based on rate responses in other studies (Brewer et al 2021). However, researchers have not evaluated topramezone absorption when applied with chlorothalonil.…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…Although the mechanism for reduction in topramezone goosegrass control by chlorothalonil-containing products cannot be ascertained through this research, Lancaster et al (2005a) found that chlorothalonil reduces sethoxydim and clethodim absorption by approximately 14% when applied in mixture. A similar reduction in topramezone absorption would be expected to reduce goosegrass control based on rate responses in other studies (Brewer et al 2021). However, researchers have not evaluated topramezone absorption when applied with chlorothalonil.…”
Section: Resultssupporting
confidence: 52%
“…However, the reduction in goosegrass control may be potentially overcome by increasing the total number of topramezone applications. Previous studies indicate that multiple topramezone applications are typically needed to control goosegrass (Brewer et al 2021; Cox et al 2017). When topramezone and chlorothalonil applications coincide, applying additional topramezone to overcome the reduced goosegrass control caused by mixing the two products may be more economical than the labor and fuel involved with applying topramezone and chlorothalonil separately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations